2014
DOI: 10.1155/2014/927190
|View full text |Cite
|
Sign up to set email alerts
|

Exploring T Cell Reactivity to Gliadin in Young Children with Newly Diagnosed Celiac Disease

Abstract: Class II major histocompatibility molecules confer disease risk in Celiac disease (CD) by presenting gliadin peptides to CD4 T cells in the small intestine. Deamidation of gliadin peptides by tissue transglutaminase creates immunogenic peptides presented by HLA-DQ2 and DQ8 molecules to activate proinflammatory CD4 T cells. Detecting gliadin specific T cell responses from the peripheral blood has been challenging due to low circulating frequencies and heterogeneity in response to gliadin epitopes. We investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 27 publications
(31 reference statements)
0
7
0
Order By: Relevance
“…24,25 In contrast, in vitro data from CD children suggested a lower rate of response to dominant T cell epitopes, a lower rate of dependence on deamidation for bioactivity, and implicated a series of novel immunogenic peptides. 15 Studies assessing peripheral blood mononuclear cells (PBMC) from untreated children with CD using in vitro culture (and no oral gluten challenge) detected responses to DQ2.5-glia-α1a and α2 in 30% or less of children 26 and proliferation was not detected. 27 Vader et al showed that only 8/16 TCL from 25 Dutch children (aged 1-12, average age 4) with CD responded to DQ2.5-glia-α1a/α2 epitopes regarded as immunodominant in adults with CD.…”
Section: Discussionmentioning
confidence: 99%
“…24,25 In contrast, in vitro data from CD children suggested a lower rate of response to dominant T cell epitopes, a lower rate of dependence on deamidation for bioactivity, and implicated a series of novel immunogenic peptides. 15 Studies assessing peripheral blood mononuclear cells (PBMC) from untreated children with CD using in vitro culture (and no oral gluten challenge) detected responses to DQ2.5-glia-α1a and α2 in 30% or less of children 26 and proliferation was not detected. 27 Vader et al showed that only 8/16 TCL from 25 Dutch children (aged 1-12, average age 4) with CD responded to DQ2.5-glia-α1a/α2 epitopes regarded as immunodominant in adults with CD.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we were able to demonstrate the presence of T cells specific to deamidated gliadin in the peripheral blood of children with active CD without gluten challenge [17]. Circulating T cells specific to various DGPs were also detected in a high percentage of children with newly diagnosed CD by Liu et al [18].…”
Section: Introductionmentioning
confidence: 81%
“…We have demonstrated previously that CD4 + T cells specific to deamidated gliadin can be detected at a higher frequency in the peripheral blood of pediatric patients at the time of CD diagnosis [17]. Liu et al have also demonstrated that gliadin-specific T-cell responses can be detected without gluten challenge in peripheral blood of children with CD [18]. However, there are no prospective follow-up studies of CD where gliadinspecific T-cell responses have been monitored in children.…”
Section: Development Of Gliadin-specific Immune Responsesmentioning
confidence: 99%
“…TCR transductants were generated as previously described using retroviral transduction of the 5KC murine T cell hybridoma cell line lacking endogenous TCR expression (55). The sequences for the α/β TCR clones were either obtained as gifts from investigators (clone 5 from Bart Roep, Leiden University, Leiden, Netherlands; 489 from Ludvig Sollid, Oslo University, Oslo, Norway; and DQ8-flu from Bill Kwok, Benaroya Research Institute, have been generated (45,46) but are only specific for single epitopes, while immune responses to many different self-antigens are present in an autoimmune disease.…”
Section: Methodsmentioning
confidence: 99%
“…The peptides used for TCR stimulation assays were obtained from Genemed Synthesis at a greater than 95% purity. Recombinant α-gliadin/DQ8 protein containing the deamidated peptide sequence QQYPSGEGSFQPSQENPQ was expressed in S2 Drosophila cells and purified as previously described (55). TATD (1,3,6,8-tetraaza-tricyclo[4.4.1.13,8]dodecane) Seattle, Washington, USA) or from published literature (clones 13, 22, and 38, which are DQ8 restricted; clone 233, which is DQ2 restricted; and C7CH17, which is DR4 restricted) (31,32,34,56).…”
Section: Methodsmentioning
confidence: 99%